2014
DOI: 10.2217/pgs.14.47
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Dose Requirements in a Patient with the CYP2C9*14 Allele

Abstract: We describe a 64-year-old male of Indian descent with a history of atrial fibrillation who was started on warfarin after hospital admission for acute stroke. He received genotype-guided warfarin dosing as per the standard-of-care at our hospital, with daily dose recommendations provided by the pharmacogenetics service. Genotyping revealed the rare CYP2C9*1/*14 genotype and warfarin insensitive VKORC1 -1639GG and CYP4F2 433Met/Met genotypes. The patient received an initial warfarin loading dose of 4 mg for 2 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…VKORC1 and CYP2C9 have significant effects on warfarin response [33]. Our study did not reveal correlation between these two genes and bleeding risks.…”
Section: Discussioncontrasting
confidence: 79%
“…VKORC1 and CYP2C9 have significant effects on warfarin response [33]. Our study did not reveal correlation between these two genes and bleeding risks.…”
Section: Discussioncontrasting
confidence: 79%
“…They have been identified as the most common defective alleles and have exhibited reduced metabolic activities, both in vitro and in vivo, for the CYP2C9 substrates, such as warfarin. In addition to these two common alleles, other allelic variants, such as CYP2C9*4 (Lee et al, 2007), CYP2C9*5 (Dickmann et al, 2001), CYP2C9*8 (Liu et al, 2012), CYP2C9*11 (Tai et al, 2005), CYP2C9*12 (O'Brien et al, 2013), CYP2C9*14 (Lee et al, 2014), CYP2C9*35 (Ciccacci et al, 2011), CYP2C9*57 (Nahar et al, 2013), and CYP2C9*58 (Luo et al, 2014), were reported to affect warfarin sensitivity. In this study, we present the case of a Chinese warfarin-sensitive patient who requires only one-half of the normal oral warfarin dose.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations in its coding gene have been found significantly associated with lowered daily warfarin dose requirement and appear to be more susceptible to the adverse effects during initiation of therapy. To date, several CYP2C9 allelic variants, such as *2, *3, *4, *5, *8, *11, *12, *14, *35, *57 and *58 have been reported to be associated with warfarin sensitivity [13,[31][32][33][34][35][36][37][38]. In this study, we detected another novel allelic variant CYP2C9*60 in a warfarin-sensitive Chinese patient.…”
Section: Resultsmentioning
confidence: 67%